Determinants of anastomotic leakage among adult bowel surgery patients at Queen Elizabeth Central Hospital, Malawi - Banda, Rodrick Vale (2021)
Anastomotic leakages are major complications of bowel surgery with significant implications on patients’ health, prognosis and on health care costs as well. The prevalence of anastomotic leaks (AL) is between 0.5% and 21% after colon and rectal resections [1–5]. The incidence is between 1% and 12% overall and up to 10% to 14% in low colorectal resections [5-8]. In Malawi as in other Sub-Saharan countries, there is limited data on AL. This study seeks to determine the factors predisposing to AL among adult bowel surgery patients at Queen Elizabeth Central Hospital (QECH) • To determine the risk factors for AL among adult bowel surgery patients at QECH Specific objectives • To determine the incidence of bowel AL among adult patients at QECH • To determine the difference in outcomes of bowel surgery performed by surgical trainees and consultant surgeons • To determine the 30-day mortality post bowel AL The study was a retrospective cohort study of the risk factors involved in the occurrence of AL within 30 days post-surgery. Patient’s files were retrieved from the QECH health information management systems for the period January 2008 to December 2016. Over the study period, 185 patients with intestinal anastomosis were identified; the overall leak rate was 16.8% (31/185) and 30-day mortality rate post AL was 35.5% (11/31). In bivariate analysis, 5 factors were associated with AL. Out of these 5 factors, 3 were found to be independent determinants of AL using a logistic regression model: intraperitoneal local sepsis (Relative risk [RR] 7.2, 95%confidence interval [CI] 2.81- 17.5), Haemoglobin level ([<10g/dl] RR 4 ,95% CI 2.167 – 7.5) and Surgeons experience( Trainee/ expert) ( RR 1.4 , 95% CI 1.143-1.957) The knowledge of factors associated with anastomotic leakage after intestinal anastomosis can be modified to reduce AL and improve AL outcomes in our setting